Colon cancer in France: evidence for improvement in management and survival. (1st July 2002) - Faivre-Finn, C; Bouvier-Benhamiche, A-M; Phelip, J M; Manfredi, S; Dancourt, V; Faivre, J
Abstract : Background: Cancer registries recording all cases diagnosed in a well defined population represent the only way to assess real changes in the management of colon cancer at the population level. Aims: To determine trends over a 23 year period in treatment, stage at diagnosis, and prognosis of colon cancer in the Côte-d'Or region, France. Patients: A total of 3389 patients with colon cancer diagnosed between 1976 and 1998. Methods: Time trends in clinical presentation, surgical treatment, chemotherapy treatment, stage at diagnosis, postoperative mortality, and survival were studied. A non-conditional logistic regression was performed to obtain an odds ratio for each period adjusted for the other variables. To estimate the independent effect of the period on prognosis, a relative survival analysis was performed. Results: Between 1976 and 1991, the resection rate increased from 69.3% to 91.9% and then remained stable. This increase was particularly marked in the older age group (56.4% to 90.5%). The proportion of stage III patients treated with adjuvant chemotherapy rose from 4.1% for the 1989–1990 period to 45.7% for the 1997–1998 period. Over the 23 years of the study the proportion of stage I and II patients increased from 39.6% to 56.6%, associated with a corresponding decrease in the proportion of patients with advanced stages. Postoperative mortality decreased from 19.5% to 7.3%. This led to an improvement in five year relative survival (from 33.0% for the 1976–1979 period to 55.3% for the 1992–1995 period). Conclusions: Advances in the management of colon cancer have resulted in improving the prognosis of this disease. However, progress is still possible, particularly in the older age group.